Spanish Adaptation and Validation of the Transplant Effects Questionnaire (TxEQ-Spanish) in Liver Transplant Recipients and Its Relationship to Posttraumatic Growth and Quality of Life - Pérez-San-Gregorio, María Á.; Martín-Rodríguez, Agustín; Sánchez-Martín, Milagrosa; Borda-Mas, Mercedes; Avargues-Navarro, María L.; Gómez-Bravo, Miguel Á.; Conrad, Rupert (Frontiers in Psychiatry, 2018)
The valid assessment of the impact of transplantation on psychological well-being is highly relevant to optimize treatment. However, to date there is no standardized instrument available in Spain. The Transplant Effects Questionnaire (TxEQ) evaluates the specific problems associated with organ transplantation, such as worry about transplant, guilt regarding the donor, disclosure of having undergone transplantation, adherence to medical treatment and responsibility towards the donor, family, friends, or medical staff. Against this backdrop the English original version of the TxEQ was translated into Spanish and validated in a sample of 240 liver transplant recipients. Participants also filled in the Posttraumatic Growth Inventory (PTGI), and the 12-Item Short Form Health Survey (SF-12v.2). Confirmatory factor analysis of the TxEQ-Spanish revealed a five-factor structure equivalent to the English original version, and satisfactory internal consistency (Cronbach’s alpha: worry α=0.82, guilt α=0.77, disclosure α=0.91, adherence α=0.82, responsibility α=0.83). Results showed that better mental quality of life was associated with higher adherence and disclosure, as well as less worry and guilt. Higher posttraumatic growth was significantly associated with worry, guilt, and responsibility. Interestingly, the most powerful predictor of posttraumatic growth was worry. Analysis of variance showed an interaction effect of PTG and mental quality of life on adherence, with medium PTG being associated with significantly stronger adherence in participants with better mental quality of life. In conclusion our study could successfully adapt and validate the Spanish version of the TxEQ in a large sample of liver transplant recipients. Our findings show a complex relationship between emotional reactions to transplantation, mental quality of life and posttraumatic growth, which give further insight into inner processes supporting psychological well-being and adherence after liver transplantation.